PENGARUH NET PROFIT MARGIN, TOTAL ASSET TURN OVER TERHADAP RENTABILITAS EKONOMI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sudrajat, Muhamad Agus (Fakultas Ekonomi Universitas Wisnuwardhana, 2016)
Abstract. The purpose of this study is to provide empirical evidence that theNet Profit Margin (NPM) significantly affects economic rentability andprovide empirical evidence that Total Assets Turn Over (TATO) significantlyaffects the economy rentability Manufacturing Companies Listed in IndonesiaStock Exchange with less control variable size firm. This study usessecondary data, financial reports companies listed on the Stock Exchange theperiod 2007-2011. Data was collected using Content Analysis method. Thesampling technique using purposive sampling method, the number of samplesin this study were 95 manufacturing companies. The results show, that theNPM significant effect on the economic rentability and TATO significanteffect on the economy rentability Manufacturing Companies Listed inIndonesia Stock Exchange in 2007-2011.Keywords : Net Profit Margin, Total Assets Turn Over, Firm Size,Economic Rentability